2003
DOI: 10.1523/jneurosci.23-23-08212.2003
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Stimulates Energy Metabolism in Developing Cortical Neurons

Abstract: Brain-derived neurotrophic factor (BDNF) promotes the biochemical and morphological differentiation of selective populations of neurons during development. In this study we examined the energy requirements associated with the effects of BDNF on neuronal differentiation. Because glucose is the preferred energy substrate in the brain, the effect of BDNF on glucose utilization was investigated in developing cortical neurons via biochemical and imaging studies. Results revealed that BDNF increases glucose utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 59 publications
5
94
0
Order By: Relevance
“…[35][36][37] The BDNF protein is induced by cortical neurons and regulates survival of striatal neurons in the brain. 38 Several experimental (in vitro and in vivo) and human studies have suggested that BDNF may exacerbate methylmercuryinduced cell death by decreasing the BDNF gene expression. 37,39 Sex-related differences in cord serum BDNF concentrations were observed in relation to prenatal exposure to methylmercury in a Faroese cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] The BDNF protein is induced by cortical neurons and regulates survival of striatal neurons in the brain. 38 Several experimental (in vitro and in vivo) and human studies have suggested that BDNF may exacerbate methylmercuryinduced cell death by decreasing the BDNF gene expression. 37,39 Sex-related differences in cord serum BDNF concentrations were observed in relation to prenatal exposure to methylmercury in a Faroese cohort.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT-3 possesses higher affinity (lower kilometers) for glucose than GLUT-1 (reviewed in Bolaños et al (2004)). Taking into account the high affinity and dependence of neurons for glucose, it has been postulated that the activity of this transporter would play a beneficial role during glucose deprivation, hypoxic episodes or other metabolic compromising situations (Burant and Bell, 1992;Gerhart et al, 1992;Fattoretti et al, 2001;Burkhalter et al, 2003). Thus, GLUT-3 activity affords neuroprotection (Hara et al, 1989;Lee and Bondy, 1993;Urabe et al, 1996;Uehara et al, 1997), and its malfunctioning is related with neuronal damage (reviewed in McEwen and Reagan (2004)).…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry-Immunostaining was performed as described previously (13). Cortical neurons were fixed for 20 min in 4% paraformaldehyde except for double-labeling experiments with GABA and MAP2 antibodies where cortical neurons were fixed in a mixture of 4% paraformaldehyde and 0.1% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blotting-Western blots were performed as described previously (13). For immunodetection of SNAT1, SNAT2, hemagglutinin, and ␤-tubulin, blots were incubated overnight at 4°C with an antibody against SNAT1 ( Statistical Analysis-Data were analyzed for statistical significance by using one-way analysis of variance followed by Bonferroni post hoc test except for time course analysis of MeAIB uptake where one-way analysis of variance was followed by Dunnett post hoc test.…”
Section: Methodsmentioning
confidence: 99%